Evaluation of process capability in non-linear profiles using Hausdorff distance. Issue 1 (2nd January 2016) - Guevara, Rubén D.; Vargas, José A.; Castagliola, Philippe
Abstract: There are practical situations in which the quality of a process or a product can be better characterized by a functional relationship between a response variable and one or more explanatory variables, called a profile. Frequently, such profiles can adequately be represented using linear or non-linear models. There are few studies that evaluate the capability of a process characterized by non-linear profiles. In this paper, we propose a method to measure the capability of such processes based on the Hausdorff distance. The performance of the proposed method is evaluated through simulation studies. An example illustrates this method.